Kaji Eksperimental Variasi Arus Dan Polaritas Pengelasan Smaw Menggunakan Sistem Sliding Adaptive Two Axis - Tazkiyah Ahcmad; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Each welding process has its own advantages depending on the placement of the implementation. One of the welding techniques is SMAW (Shielded Metal Arc Welding), which has its own advantages, including largecurrents such as heat source that can be varied, easy to use in different welding positions and penetration and the melting height of the electrode can be adjusted. In the SMAW welding process, the variable that determines the quality of the welding results is the choice of the correct added material, the selection of the current used inthe machine must be adjusted such that the added material (the electrode) is perfect and the welding speed (angle) of the welding itself. The selection of these variables depends on the skill (skill) of the operator who implements them, so that the determination of these variables often changes. In contrast to the welding process that is performed using the SMAW welding machine with a sliding adjustable system with two axes to replace the welder, so that the speed and position parameters of welds can be obtained constantly (fixed).The varied parameters are current and polarity using DC currents (unidirectional) with currents of 90A, 100A and120A.The material used in this study uses mild steel, the seam used is V with an angle of 60o and electrodes with the AWS E-6013 standard. The number of samples tested was 18 samples, 9 of which for straight polarityand 9 samples for reverse polarity. The microstructure of the welding is determined by many factors, including heat input, current, welding speed and cooling speed. In this study, the HAZ area had a grain structure that was larger than base metal and weld metal.Keywords : Currents, Polarity, SMAW Welding, Sliding Adaptive Two Axis